Prescription Opioid Laws and Opioid Dispensing in US Counties: Identifying Salient Law Provisions With Machine Learning. Issue 6 (November 2021) - Martins, Silvia S.; Bruzelius, Emilie; Stingone, Jeanette A.; Wheeler-Martin, Katherine; Akbarnejad, Hanane; Mauro, Christine M.; Marziali, Megan E.; Samples, Hillary; Crystal, Stephen; Davis, Corey S.; Rudolph, Kara E.; Keyes, Katherine M.; et al.
Abstract : Background: Hundreds of laws aimed at reducing inappropriate prescription opioid dispensing have been implemented in the United States, yet heterogeneity in provisions and their simultaneous implementation have complicated evaluation of impacts. We apply a hypothesis-generating, multistage, machine-learning approach to identify salient law provisions and combinations associated with dispensing rates to test in future research. Methods: Using 162 prescription opioid law provisions capturing prescription drug monitoring program (PDMP) access, reporting and administration features, pain management clinic provisions, and prescription opioid limits, we used regularization approaches and random forest models to identify laws most predictive of county-level and high-dose dispensing. We stratified analyses by overdose epidemic phases—the prescription opioid phase (2006–2009), heroin phase (2010–2012), and fentanyl phase (2013–2016)—to further explore pattern shifts over time. Results: PDMP patient data access provisions most consistently predicted high-dispensing and high-dose dispensing counties. Pain management clinic-related provisions did not generally predict dispensing measures in the prescription opioid phase but became more discriminant of high dispensing and high-dose dispensing counties over time, especially in the fentanyl period. Predictive performance across models was poor, suggesting prescription opioid laws alone do not strongly predict dispensing. Conclusions: Our systematic analysis of 162 law provisions identified patient data access and several pain management clinic provisions as predictive of county prescription opioid dispensing patterns. Future research employing other types of study designs is needed to test these provisions' causal relationships with inappropriate dispensing and to examine potential interactions between PDMP access and pain management clinic provisions. See video abstract at, http://links.lww.com/EDE/B861 . Abstract : Supplemental Digital Content is available in the text.